P222 Psychological impact in cough hypersensitivity syndrome. (12th November 2019) - Ludlow, SF; Haines, J; Hope, H; Marsden, P; Fowler, S
Abstract : Background: Cough hypersensitivity syndrome is associated with significant physical and psychological morbidity and impacts patient's quality of life. We aimed to evaluate the prevalence of anxiety and depression symptoms in our patients with cough hypersensitivity syndrome and to assess patients' awareness of the association. Method: All patients over a three month period who attended a Respiratory Speech and Language Therapy-led cough assessment clinic were asked to complete the Leicester Cough Questionnaire (LCQ), Generalised Anxiety Disorder Assessment (GAD-7), Patient Health Questionnaire depression module (PHQ-9) and cough severity Visual Analogue Scale (VAS, 0–10 scale). Patients were asked if they believed anxiety, depression or stress were triggers for their cough. Results: Data from 32 patients (24 female) with a median (range) age of 57 (31–73) years and average cough duration of 10 (2–40) years who attended the clinic between April and June 2019 were analysed (table). Other relevant co-morbidities included asthma (16%), inducible laryngeal obstruction (13%), reflux (38%) and nasal disease (28%). Several patients were taking (38%) or had taken (38%) anti-tussive medications for their cough. On the GAD-7, 12 patients reported anxiety symptoms (38%); seven mild (22%), three moderate (9%) and two severe (6%). On the PHQ-9, 15 patients reported depression symptoms (47%); ten mild (31%), four moderate (13%) and one severe (3%). Several patients who recognised stress to be a trigger of their cough scored highly on the anxiety and depression questionnaires (12/17, 70%). Cough scores (VAS and LCQ) correlated strongly with each other, as did GAD7 and PHQ9 scores. PHQ9 also correlated with the LCQ-physical domain (Spearman's rho=-0.397, p=0.025) supporting the relationship between depression and increased physical symptoms related to cough. Conclusion: A high proportion of patients with cough hypersensitivity syndrome had symptoms of anxiety and depression. The direction of cough and psychological problems is difficult to determine from these results. When taking a medical history from a patient, physicians should note psychological as well as physical complications. Failure to recognise this may influence treatment outcomes. Clinical psychology input into cough multi-disciplinary teams may be beneficial.